2012
DOI: 10.3109/09593985.2012.676722
|View full text |Cite
|
Sign up to set email alerts
|

Joint position sense is not altered during shoulder medial and lateral rotations in female assembly line workers with shoulder impingement syndrome

Abstract: This study evaluated joint position sense (JPS) during medial and lateral rotations of the shoulder in female workers with and without shoulder impingement syndrome (SIS). Three groups were assessed. The case group consisted of 15 female assembly line workers (35.5, SD 5.8 years) with unilateral SIS. Control group 1 consisted of 15 female assembly line workers asymptomatic for SIS (34.4, SD 5.5 years) and control group 2 consisted of 15 female subjects (33.1, SD 6.2 years) asymptomatic for SIS and with no expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
(80 reference statements)
0
22
0
1
Order By: Relevance
“…Previous studies using the isokinetic dynamometer also reported no reduction in proprioception in women with SAPS 11 and people with experimentally induced subacromial pain. 10 Further studies should compare proprioception of the shoulder in a painful arc and asymptomatic motion of the patients with SAPS to clarify our hypothesis.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Previous studies using the isokinetic dynamometer also reported no reduction in proprioception in women with SAPS 11 and people with experimentally induced subacromial pain. 10 Further studies should compare proprioception of the shoulder in a painful arc and asymptomatic motion of the patients with SAPS to clarify our hypothesis.…”
Section: Discussionmentioning
confidence: 79%
“…We conducted a randomization procedure for the proprioceptive evaluations to prevent learning bias by movement repetition. The same procedure was carried out in one study that did not find a reduction in proprioception for these patients . The comprehensive assessment of shoulder proprioception in patients with SAPS was carried out using an isokinetic dynamometer, which is a gold standard instrument for proprioception analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations